Precipitating events in child and adolescent chronic musculoskeletal pain. (September 2018) - Becker, Andrew J.; Heathcote, Lauren C.; Timmers, Inge; Simons, Laura E.
Abstract: Introduction: The epidemiology of chronic pain in youth has been increasingly documented over the past decade. However, the precipitating events associated with the onset of pediatric chronic pain are not well studied. Objectives: Understanding the events that precede the onset of pain, and are reported by patients as germane to the early stages of their pain, may add one piece to the puzzle of the causal etiology of pediatric chronic pain disorders. Methods: We conducted a retrospective chart review of 320 young people attending a tertiary care chronic pain clinic with musculoskeletal chronic pain. Results: Approximately two-thirds of patients reported a precipitating event for their pain; injury was the most commonly reported event, followed by a chronic disease, then an infection or illness. Surgery was the least commonly reported event. About one-third of patients did not report any precipitating event for their pain. Patients with neuropathic pain were even more likely to report a precipitating event compared to those with localized and diffuse musculoskeletal pain. Patients with localized musculoskeletal pain and neuropathic pain were most likely to report an injury, whereas patients with diffuse musculoskeletal pain were most likely to report a chronic disease. We found little to no evidence that the presence or type of precipitating event was associated with patients' psychological or physical functioning. Conclusion: This study adds to the epidemiological evidence base for pediatric chronic pain disorders.